ESTABLISHMENT OF LIMITS TO THE PRINCIPAL DIMENSIONS OF THE ROTOR OF A HIGH SPEED HIGH POWER DENSITY ELECTRICAL MACHINE AS AFFECTED BY THE MECHANICAL LIMITS - Msekela, J. A.N. (Tanzania Journal of Engineering and Technology, 2018)
Abstract